UV-guided isolation of polyynes and polyenes from the roots of Codonopsis pilosula1. Issue 52 (10th June 2015) - Chao, Chih-Hua; Juang, Shin-Hun; Chan, Hsiu-Hui; Shen, De-Yang; Liao, Yu-Ren; Shih, Hung-Cheng; Huang, Chieh-Hung; Cheng, Ju-Chien; Chen, Fu-An; Hung, Hsin-Yi; Wu, Tian-Shung
<x xml:space="preserve">Abstract</x> UV-guided isolation of polyacetylenes from Codonopsis pilosula has successfully led to the characterization of new polyynes and polyenes. The HCVcc infection assay was used to evaluate the anti-HCV activity of compounds 1–12.